2013
DOI: 10.1371/journal.pone.0066990
|View full text |Cite
|
Sign up to set email alerts
|

Invariance of visual operations at the level of receptive fields

Abstract: The brain is able to maintain a stable perception although the visual stimuli vary substantially on the retina due to geometric transformations and lighting variations in the environment. This paper presents a theory for achieving basic invariance properties already at the level of receptive fields. Specifically, the presented framework comprises (i) local scaling transformations caused by objects of different size and at different distances to the observer, (ii) locally linearized image deformations caused by… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 100 publications
(134 reference statements)
0
23
0
Order By: Relevance
“…Then, the image operations can be made truly covariant under local, regional or global Galilean image transformations [67,71] and allow for a more explicit separation of spatio-temporal receptive field responses that correspond to more complex spatio-temporal image structures than local Galilean motions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Then, the image operations can be made truly covariant under local, regional or global Galilean image transformations [67,71] and allow for a more explicit separation of spatio-temporal receptive field responses that correspond to more complex spatio-temporal image structures than local Galilean motions.…”
Section: Resultsmentioning
confidence: 99%
“…Cell recordings from neurones in the primary visual cortex have shown that there are spatio-temporal receptive fields tuned to different sizes and orientations in the image domain, to different integration times over the temporal domain as well as to different image velocities in space-time [12,13,32,33]. Interestingly, the shapes of the spatio-temporal receptive field families that have been measured in biological vision can furthermore be explained by normative theories of visual receptive fields [69,71,75,78], whose axiomatic derivation is based on structural properties of the environment in combination with assumptions about the internal structure of an idealized vision system to ensure a consistent treatment of image representations over multiple spatio-temporal scales.…”
Section: Introductionmentioning
confidence: 99%
“…Thereby, the detection scale can be used for defining a local scale normalized reference frame around the interest point [109,111] implying that image descriptors defined relative to such a scale-normalized reference frame will also be provably scale invariant.…”
Section: Discussionmentioning
confidence: 99%
“…A general theoretical framework for how local receptive field responses, as used in the SIFT and SURF descriptors and their extensions or analogues to colour images and spatiotemporal image data, can constitute the basis for computing inherent properties of objects to support invariant recognition under natural image transformations is presented in (Lindeberg [106,109]) including relations to receptive fields in biological vision.…”
Section: Related Workmentioning
confidence: 99%
“…The idea of affine shape adaptation underlying one of the methodologies for achieving affine invariance, was then in turn used as a base for the work on affine invariant interest points and affine invariant matching in [28,6,37,38,58,57,56]. The notion of an affine invariant reference frame was further developed in [30,31]. Nevertheless, to the best of our knowledge, the direct constructions of affine invariant descriptors as fixed points for an iterative affine normalization process have never found a mathematical justification.…”
Section: Introductionmentioning
confidence: 99%